Dasytes plumbeus (Müller) (Coleoptera: Melyridae: Dasytinae), a Palearctic soft-winged flower beetle new to North America - Hoebeke, E. Richard; Wheeler, Alfred G. Jr. (Zootaxa, 2013)
Dasytes plumbeus (Müller), a dasytine melyrid beetle native to the Palearctic Region, is newly reported from North America. In 2010 and 2011, specimens from three locations were swept from vegetation and flowers in the greater Vancouver area of British Columbia, Canada. This is the first confirmed record of the species in the New World. Our collections, coupled with Internet images of D. plumbeus found in the Vancouver area, suggest the beetle is established in British Columbia.